Investigating Parenting Activity for Students With Intelectual Disability During Online Learning: Reading, Writing, Counting Skills - Irvan, Muchamad; Rabbani, Faizzuddin; Mutmainah, Siti (Journal of Education for Sustainability and Diversity, 2024)
Intellectual disabilities are children with low intellectual abilities and impact difficulties in understanding learning. To achieve optimal learning outcomes, the role of parents at home in mentoring is crucial. The study aimed to find out to what extent the assistance provided by parents in learning at home can affect the reading, writing, and numeracy abilities of students with intellectual disabilities. This study uses qualitative research. The research subjects consisted of nine people: three parents, three teachers, and three students with mild intellectual disability in grade 5 SDLB BC Kepanjen. Data collection techniques using interview techniques, observation, and documentation. Data analysis was done by data reduction, describing and compiling data systematically to conclude. The source and technical triangulation are the methods of checking the data’s validity. The research concludes that academic learning at home is not optimal. In general, this is caused by parents not playing an active role in accompanying students with intellectual disability studying at home.